PHRONESIS AS APPOSITE WISDOM - Stephen Curkpatrick (SAGACITY : Journal of Theology and Christian Education, 2020)
Phronesis or applied wisdom is a specifically Christian quality, yet is not exclusive to Christian tradition and engagement. Phronesis is articulated with specific stylistics, such as situational decisionmaking or customary interaction within human existence. In this article, philosophical perspectives are generated from an interface of phronesis and life—volition, responsibility, freedom and common sense. Exploration of these perspectives will be used to articulate the character of phronesis and its expression within human purpose, vocation and identity. Engagement with phronesis here articulates epistemological and hermeneutical challenges that can preface specifically Christian expression that contributes to human flourishing through generosity and veracity.